2021
DOI: 10.1186/s12967-021-02786-6
|View full text |Cite
|
Sign up to set email alerts
|

GRP78 in lung cancer

Abstract: Glucose-regulating protein 78 (GRP78) is a molecular chaperone in the endoplasmic reticulum (ER) that promotes folding and assembly of proteins, controls the quality of proteins, and regulates ER stress signaling through Ca2+ binding to the ER. In tumors, GRP78 is often upregulated, acting as a central stress sensor that senses and adapts to changes in the tumor microenvironment, mediating ER stress of cancer cells under various stimulations of the microenvironment to trigger the folding protein response. Incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
48
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(48 citation statements)
references
References 130 publications
0
48
0
Order By: Relevance
“…GRP78 plays an important role in the antiapoptotic mechanisms of cancer cells [ 14 ]. Several studies have proven that GRP78 expression positively correlates with tumor development in renal cell carcinoma [ 15 ], lung cancer [ 16 ], and ovarian cancer [ 17 ]. Our data supported that Hotair upregulates GRP78 via hsa-miR-30a-5p, and downregulation of Hotair also inhibited cell proliferation and promoted apoptosis in LSCC.…”
Section: Resultsmentioning
confidence: 99%
“…GRP78 plays an important role in the antiapoptotic mechanisms of cancer cells [ 14 ]. Several studies have proven that GRP78 expression positively correlates with tumor development in renal cell carcinoma [ 15 ], lung cancer [ 16 ], and ovarian cancer [ 17 ]. Our data supported that Hotair upregulates GRP78 via hsa-miR-30a-5p, and downregulation of Hotair also inhibited cell proliferation and promoted apoptosis in LSCC.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have reported that BiP is involved in the regulation of tumor function, including epithelial–mesenchymal transition (EMT) change, migration, invasion, and tumor-associated angiogenesis, and that VEGF is a downstream regulator of BiP participating in these pathological processes [ 45 47 ]. Therefore, the effect of CSC on the expression of VEGF and malignant behaviors were evaluated in YD38 and SCC25 cells after treatment with 120 μg/ml CSC for 48 h. We found that CSC increased the expression of VEGF in OSCC cells, and that the levels of secreted VEGF were significantly higher in the CM collected from OSCC cells incubated with CSC compared to those from the control cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was shown that the GRP78 level is regulated either directly or indirectly by ATF4 [19]. Phosphorylation of eukaryotic initiation factor-2α (eIF2α) activates ATF4, which regulates the UPR by controlling the expression of UPR target genes that are linked to endoplasmic-reticulum-associated protein degradation (ERAD) and pro-apoptotic CCAAT/enhancer-binding protein (C/ EBP)-homologous protein (CHOP) [19]. In addition, a conserved binding site (5′-TGA CGT GA-3′) for ATF4 is located upstream to the ER stress response element (ERSE) in the mammalian GRP78 promoter.…”
Section: Atf4 As Er Stress Modulator In the Cross-talk With Oxidative...mentioning
confidence: 99%